A Novel Coordinated Control System to Reactive Power Compensation of Photovoltaic Inverter Clusters - Tingzhe Pan (International Transactions on Electrical Energy Systems)
With the development of new energy, a cost-effective reactive power compensation scheme is essential to the voltage stability of the power system for small-capacity distributed generation. This paper proposes a coordinated control scheme of inverter cluster which is based on the reactive power support capability of the photovoltaic inverter. Moreover, by using power angle vectors, a reactive power distribution algorithm is proposed to solve the poor power quality of the point of common coupling connecting source and load in the distributed generation station. Simulations verify the performance of the algorithm is better than the conventional static capacity distribute algorithm and dynamic residual margin distribute algorithm. Finally, the effectiveness of the reactive power compensation scheme and distribution strategy for improving power quality and regulation ability proposed in this paper is verified by operation experiments in the actual power station.